What influence users' e-finance continuance intention? The moderating role of trust. Issue 8 (10th September 2018) - Zhou, Wangyue; Tsiga, Zayyad; Li, Boying; Zheng, Shuning; Jiang, Shuli
Abstract : Purpose: The purpose of this paper is to identify antecedents of e-finance continuance intention with Alibaba's Yu'E Bao as an example. Design/methodology/approach: An online questionnaire was used to collect the data ( n =293), and partial least squares structural equation modeling was employed for data analysis. Four e-finance features (perceived reputation, website quality, e-finance familiarity and situational normality) are introduced with trust acting as a moderator between the users' satisfaction and continuance intention to use an e-finance platform. Findings: The results find that website quality, familiarity and situational normality can influence perceived ease of use (PEOU) and perceived usefulness (PU). PEOU and PU, together with reputation, are positively associated with confirmation which further leads to satisfaction. The positive effects that satisfaction and trust have on e-finance continuance intention are confirmed, and trust is found to be a significant moderator on the relationship between satisfaction and continuance intention. Practical implications: The findings can be used to guide e-finance providers to improve their platform design and services to retain users. Originality/value: This study combines the theory of trust, Technology Acceptance Model and Expectations Confirmation Theory to investigate the factors that influence the continuance intention in the context of e-finance in China.